Sekolah Dasar Luar Biasa (SDLB) dengan Pendekatan Arsitektur Perilaku di Kabupaten Mamuju - adiyani, Lulu anggreani; Irma Rahayu; Andi Hildayanti (TIMPALAJA : Architecture Student Journals, 2024)
Abstract_Indonesia has 2,250 Special Schools (SLB) for Children with Special Needs (ABK) from elementary to high school in the 2021–2022 academic year. This study aims to design a Special Elementary School (SDLB) with a behavioural architecture approach in Mamuju Regency to produce a design that meets the needs of ABK. The research methods include data collection from literature studies and descriptive analysis based on field surveys of site conditions. The results indicate that site selection, condition, and area must be based on criteria and regional spatial plans to ensure that the building design aligns with actual conditions on the ground and incorporates behavioural architecture. The planning of the SDLB must consider ABK's particular needs, accessibility, comfort, and safety. Applying the behavioural architecture concept in SDLB design considers the behaviour of ABK and connects it with the use of the designed building. The design of SDLB with a behavioural architecture approach focuses on creating a safe and standard-compliant building by considering the needs and activities of ABK from an architectural perspective.